Fun with Dick and Jane [videorecording (DVD)] - Parisot, Dean; Carrey, Jim, 1962-; Leoni, Téa, 1966-; Baldwin, Alec, 1958- (Sony Pictures Home Entertainment, 2006)
In the year 2000, Dick gets a plum promotion as a mega-corporate communications director. His boss is preparing to bail out of the company just before stock prices plummet. Dick's wife Jane has quit her job as a travel agent, so when the corporate stocks hit rock bottom, Dick and Jane are left penniless and desperate. They decide to resort to petty thievery and this eventually gets them plotting high-stakes revenge against the greedy executives who ruined their lives.